Difference of Children Ages 5-6 Years of Independence Viewed from The Caregiver (Parents and Grandparents) in Kindergarten Kartini 1 and Kartini 2 - Rahmawati, Enni; Diana, Diana (BELIA: Early Childhood Education Papers, 2016)
The child’s independence is characters that make a child in  aged 0-6 years can stand by theirselves without depending in others, especially their parents. While many parents are working, parenting will in the hand of close relatives i.e. Grandma/Grandpa. This research aims to find out if there is a difference of  child’s independence in terms of  the subject matter of  parenting (parents and grandparent). The population of  this research are all students in kindergarten  Kartini 1, and  Kartini 2. The techniques that use in this research is purposive sampling technique. This research using a sample of  children in the range of  aged 5-6 years in class B that is parenting  by parents and grandparent with a total number of  30 students. The Method analysis data collection is using child’s independence scale . Methods analysis data in this research using program SPSS16. This is demonstrated by the acquisition of the value t calculate < t table (0,268 < 2,048)and the value of  sig. > 0.05 (0,791 > 0.05), then Ho denied. The conclusions of  this research showed that there are differences between child’s independence that was parenting by their parents and grandparent.